Exploring the anti-inflammatory and anti-apoptotic properties of phloroglucinol on pancreatic cells in diabetic models: In silico and in vivo study - Puspitasari, Renny N.; I'tishom, Reny; Kurnijasanti, Rochmah; Mustafa, Mohammad R.; Sudjarwo, Sri A. (Narra Sains Indonesia, 2024)
Pancreatic cell damage in diabetes mellitus is closely linked to inflammation and apoptosis. This study aimed to investigate the protective effects of phloroglucinol on pancreatic cells in a streptozotocin-induced diabetic model by assessing its anti-inflammatory and anti-apoptotic mechanisms. Phloroglucinol ligand and the structures of Bax, Bcl-2, and caspase-3 proteins were sourced from the PubChem database. Molecular docking was performed using Autodock Tools and docking results were analyzed with PyRx software. In addition, during the in vivo study, the BALB/c mice were grouped into four categories: healthy control, untreated streptozotocin-induced diabetic, and streptozotocin-induced diabetic treated with two doses of oral phloroglucinol at 100 mg/kg and 200 mg/kg body weight. After 28 days, pancreatic tissues were collected for flow cytometric analysis of NF-κB, IL-6, TNF-α, and apoptotic markers (Bax, Bcl-2, and caspase-3). The docking simulations revealed specific binding interactions: phloroglucinol interacted with Bcl-2 via amino acid residues of ALA90 and TYR139, with Bax via ALA42, LEU45, ALA46, LEU47, PRO130, and ILE133, and with caspase-3 through ARG64, SER120, GLN161, CYS163, and ARG207. The binding affinities for Bax, Bcl-2, and caspase-3 were -5.0, -4.7, and -4.9 kcal/mol, respectively. In vivo, results showed that streptozotocin significantly elevated inflammatory cytokines NF-κB, TNF-α, and IL-6, along with apoptotic markers in pancreatic cells (p<0.05) compared to healthy controls. Phloroglucinol administration at 200 mg/kg significantly reduced TNF-α, NF-κB and IL-6 levels. Phloroglucinol also prevented streptozotocin-induced pancreatic cell damage through anti-apoptotic effects by downregulating Bax and caspase-3 and upregulating Bcl-2. These findings suggest that phloroglucinol may offer protective benefits in diabetic conditions by modulating apoptotic and inflammatory pathways.